PENGARUH PERCEIVED EASE OF USE DAN PERCEIVED USEFULNESS TERHADAP CUSTOMER LOYALTY PENGGUNA GOPAY PADA MAHASISWA/I DI UNIVERSITAS NEGERI JAKARTA DENGAN TRUST SEBAGAI VARIABEL INTERVENING - Damar Lintang; Eva Theresya Pradina, Julius Adi Wiratama, Putri Nursadrina Murni, Zahra Aisyah Andari Prayudi (CV. Adiba Aisha Amira, 2025)
This research examines the influence of Perceived Ease of Use and Perceived Usefulness on Customer Loyalty among GoPay users at Universitas Negeri Jakarta, with Trust as an intervening variable. The study employs a quantitative method, utilizing online questionnaires distributed through Google Forms to 116 respondents selected via purposive sampling. Data analysis was conducted using Structural Equation Modeling (SEM) with Partial Least Squares (PLS) approach through SmartPLS 4 software. The findings reveal that Perceived Usefulness positively and significantly affects both Customer Loyalty and Trust . While Perceived Ease of Use shows no direct significant effect on Customer Loyalty , it significantly influences Trust . Trust demonstrates a significant positive effect on Customer Loyalty and successfully mediates the relationship between both Perceived Ease of Use and Perceived Usefulness toward Customer Loyalty.